1992
DOI: 10.1002/tera.1420460305
|View full text |Cite
|
Sign up to set email alerts
|

Developmental toxicity of dichloroacetate in the rat

Abstract: Dichloroacetic acid (DCA) is a principal by-product of the chlorine disinfection of water containing humic and fulvic acids, and is also a drug of interest in the therapeutic management of metabolic disorders. The developmental effects of DCA were evaluated in the pregnant Long-Evans rat. In two separate studies, animals were dosed by oral intubation on gestation days 6-15 (plug = 0) with 0, 900, 1,400, 1,900 or 2,400 mg/kg/day and 0, 14, 140, or 400 mg/kg/day. The vehicle control was distilled water. Maternal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
57
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(61 citation statements)
references
References 20 publications
3
57
1
Order By: Relevance
“…In contrast, we found no effect of DCA on body weight at any of the exposure levels used in this study. DCA may cause hepatic hypertrophy or hyperplasia in rats (Anderson et al, 1975;Mariash and Schwartz, 1986;Mather et al, 1990;Smith et al, 1992). Although high-dose DCA (50 mg/kg/day) also increased liver weight and the liver to body weight ratio in this study, these indices returned to baseline levels after DCA was withdrawn.…”
Section: Gstz Enzyme Activity and Protein Expression In Control Ratscontrasting
confidence: 51%
“…In contrast, we found no effect of DCA on body weight at any of the exposure levels used in this study. DCA may cause hepatic hypertrophy or hyperplasia in rats (Anderson et al, 1975;Mariash and Schwartz, 1986;Mather et al, 1990;Smith et al, 1992). Although high-dose DCA (50 mg/kg/day) also increased liver weight and the liver to body weight ratio in this study, these indices returned to baseline levels after DCA was withdrawn.…”
Section: Gstz Enzyme Activity and Protein Expression In Control Ratscontrasting
confidence: 51%
“…Earlier reports have shown that DCA causes developmental and reproductive adversities in exposed organisms (rat and zebrafish) wherein very high concentrations of DCA (~400-4,000 mg/kg) were used (Hassoun et al 2005;Linder et al 1997;Smith et al 1992). However, none of the tested DCA concentrations were found to induce developmental and reproductive adversities in exposed Drosophila as evidenced by nonapparent change in the emergence pattern and reproductive performance of exposed flies.…”
Section: Discussionmentioning
confidence: 94%
“…In a number of in vitro studies, DCA is reported to enhance reactive oxygen generation (ROS) generation and oxidative stress leading to cell death (Ayyanathan et al 2012;Hassoun and Ray 2003;Wong et al 2008). In exposed in vivo models, mainly rodents, DCA is reported to cause developmental- (Smith et al 1992), spermato- (Linder et al 1997), immuno-, and hepatotoxicity (Cai et al 2007;Hassoun and Dey 2008). However, concern about DCA adversity underlies on the data generated in rodents after their exposure to this chemical at doses (up to~4,000 mg/kg) thousands of times higher than those to which humans are usually exposed (Stacpoole et al 1998).…”
mentioning
confidence: 99%
“…The trihalomethanes (THMs) are not considered teratogenic, but growth retardation has been reported in mice exposed to chloroform (Murray et al 1979;Ruddick et al 1983;Schwetz et al 1974;Thompson et al 1974). Growth retardation has also been reported in mice exposed to dichloroacetic acid (Smith et al 1992) and trichloroacetic acid (Smith et al 1989a) and in rats exposed to dichloroacetonitrile (Smith et al 1989b) and trichloroacetonitrile (Smith et al 1987).…”
mentioning
confidence: 99%